Damage detection of a steel?concrete composite frame by a multilevel approach Experimental measurements and modal identification. - Chellini, Giuseppe
Structural Health Monitoring (SHM) and Experimental Modal Analysis (EMA) have revealed to be really efficient tools for the damage detection of structures and structural elements in many engineering fields (Shock Vib. Dig. 1998; 30(2):91?105; Philos. Trans. R. Soc. A 2007; 365(1851):303?315; Mech. Syst. Signal Process. 2003; 17(1):133?142; Philos. Trans. R. Soc.: Math. Phys. Eng. Sci. 2001; 359(1778): 131?149; Struct. Control Health Monit. 2006; 14:1083?1100; Mech. Syst. Signal Process. 2004; 17(1): 83?89). Unfortunately the great variety of morphologies, construction materials and structural schemes makes these techniques not easily applicable to buildings, due to inherent problems related to the location and the extent of damage, the sensitivity of the dynamic response to damage, the choice of damage indexes to be used, the sensors' location, etc. On the other hand, the modern seismic capacity design of buildings in earthquake-prone areas tends to locate dissipative zones in well-determined portions of structures (CEN, European Committee for Standardization, EN 1998-1. Eurocode 8: Design of Structures for Earthquake Resistance. Part 1: General Rules, Seismic Actions and Rules for Buildings, European Community, Brussels, Belgium, 2005); thus, the application of vibration-based damage detection techniques to earthquake-resistant structures seems to be very promising even if nowadays there are only few studies on these arguments. The present paper reports the experiences of a vibration-based damage identification study applied to a steel?concrete composite frame structure, suitably designed to be high ductile according to Eurocode 8 and localizing the seismic energy dissipation in the beam-to-column joints. The structure was subjected to series of pseudo-dynamic (PsD) and cyclic tests with increasing peak ground acceleration at the European Laboratory for Structural Assessment of Joint Research Centre at Ispra (VA, Italy). The damaging phenomena, caused by PsD tests, were assessed and quantified by means of a multi-level vibration-based approach suitably designed in order to evaluate the changes in the global dynamic structural response and to experimentally estimate the reduction in joint stiffness.
Keywords: Steel?concrete composite frame; Capacity design; Partial-strength joints; System identification; Damage assessment; Vibration monitoring